N-acylethanolamide metabolizing enzymes are upregulated in human neural progenitor-derived neurons exposed to sub-lethal oxidative stress - Duncan, R. Scott; Riordan, Sean M.; Hall, Conner W.; Payne, Andrew J.; Chapman, Kent D.; Koulen, Peter (Frontiers in Cellular Neuroscience, 2022)
N-acyl amides (NAAs) are a class of lipids that consist of an acyl group N-linked to an amino acid, neurotransmitter, taurine or ethanolamide group and include some endocannainoids such as anandamide. These lipids are synthesized in a wide variety of organisms and in multiple cell types, including neurons. N-acylethanolamides (NAEs) are involved in numerous cellular and physiological processes and their concentrations are elevated in response to ischemia and physical trauma to play a role in neuroprotection. Since these eCB NAEs have been shown to exhibit neuroprotective properties, the protein targets for these compounds, such as cannabinoid receptor type 1 (CB1), cannabinoid receptor type 2 (CB2), fatty acid amide hydrolase (FAAH), N-acylethanolamine acid amidase (NAAA) and N-acyl phosphatidylethanolamine phospholipase D (NAPE-PLD), should be characterized in more contemporaneous model systems of neurodegeneration and neuroprotection to better understand their role and mechanism of action in neuroprotection against oxidative stress. Human stem cell-derived or human neural progenitor cell-derived cells, such as ReN cells, have become more utilized for the study of human neuronal development and neurodegenerative diseases. ReN cells can be easily differentiated thereby circumventing the need for using transformed cell lines and primary neurons as cell model systems. In this study, we determined whether ReN cells, a superior cell model system for studying neurodevelopment, differentiation and neuroprotection, express proteins involved in canonical eCB NAE signaling and whether oxidative stress can induce their expression. We determined that sublethal oxidative stress upregulates the expression of all eCB proteins tested. In addition, we determined that oxidative stress increases the nuclear localization of FAAAH, and to a lesser extent, NAAA and NAPE-PLD. This study is a first step toward determining how oxidative stress affects CB1, CB2, FAAH, NAAA and NAPE-PLD expression and their potential defense against oxidative stress. As such, our data is important for further determining the role of eCB metabolizing proteins and eCB receptors against oxidative stress.